Proposta de diretrizes para elaboração de política de indexação em bibliotecas universitárias: Um estudo sociocultural com protocolo verbal - Dal'Evedove, Paula Regina; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2017)
A set of eight guiding guidelines for the preparation of indexing policies in Brazilian university libraries is presented, as a result of a verbal-protocol study among a group of indexers from Brazilian university libraries.
A proposal of guidelines for the development of an indexing policy in university libraries: A verbal-protocol-based socio-cultural study
Keywords: Brazil; Indexing policies; Sociocultural approach; Subject cataloguing; University libraries; Verbal protocol